Organization of knowledge control in practical classes on coordination chemistry (Pedagogy of Higher and Secondary Education, 2021)
Harmonization intellectual and emotional teaching constituents on every his stage is the guarantee of receipt the students of fundamental of hifh-quality education. Introduction of intellectual-emotional approaches in an educational process is illustrated on the example of organization of control of knowledges on practical trainings of cooedination chemistry.
Keywords: pedagogical education; harmonization of education; control of knowledge